1994
DOI: 10.2169/internalmedicine.33.745
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Endoscopic Variceal Sclerotherapy on Systemic and Splanchnic Hemodynamics in Patients with Cirrhosis.

Abstract: The aim of this study was to determine whether endoscopic variceal sclerotherapy affects systemic or splanchnic hemodynamics.Wemeasured hemodynamic parameters before and after the first course of sclerotherapy in 35 patients with cirrhosis. Following sclerotherapy, there was a significant decrease in cardiac index and a significant increase in systemic vascular resistance. Changes in hepatic venous pressure gradient varied from patient to patient with no statistically significant change in the group overall. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We have previously reported that patients with esophageal varices whose hepatic venous pressure gradient decreased after EIS showed a decrease in cardiac index or a large extravariceal shunt after EIS. 33 Our present patient's portal pressure decreased after EIS. This was attributed to the presence of a splenorenal shunt.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…We have previously reported that patients with esophageal varices whose hepatic venous pressure gradient decreased after EIS showed a decrease in cardiac index or a large extravariceal shunt after EIS. 33 Our present patient's portal pressure decreased after EIS. This was attributed to the presence of a splenorenal shunt.…”
Section: Discussionmentioning
confidence: 43%
“…33 At present, little is known about the effects of EIS on hemodynamics and subsequent hepatic function in patients with duodenal varices. In our patient, the portal pressure was 22 mmHg before EIS, and this was reduced to 16 mmHg after EIS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a decrease of azygos blood flow by approximately 54% in patients who have prophylactic endoscopic injection variceal sclerotherapy. 23 Although the reason for the intra-study difference in azygos blood flow decrease is not clear, it is probably due to differences in the methods used to accomplish esophageal variceal obliteration. However, these results suggest that the majority of azygos blood flow is collateral blood flow through esophageal varices and that this is significantly reduced by successful EVL.…”
Section: Discussionmentioning
confidence: 99%